Infant and young child feeding (IYCF) practices and children's nutritional status in Democratic Republic of Congo (DRC): Evidence from Demographic and Health Surveys - Janvier Mwisha-Kasiwa; Cédrick Kalemasi Mosengo; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2024)
This paper uses a pooled dataset of the 2007 and 2014 Demographic and Health Surveys (DHS) to establish the empirical linkages between infant and young child feeding (IYCF) practices and children's nutritional status in Democratic Republic of Congo (DRC). The paper examines all the recommended dimensions of child feeding and builds an index from variables related to breastfeeding, use of bottle-feeding, minimum dietary diversity and number of times child ate solid, semi-solid or soft foods. A series of descriptive analyses and survey-based econometric regressions are carried out while controlling for endogeneity and heterogeneity. The key finding is that infant and young child feeding practices are an important and significant determinant of children's nutritional status as measured by the height-for-age z-score and the probability of stunting. In particular, an increase in the IYCF practices index by 1 unit increases by 0.47 standard score in the height-for-age z-score while it reduces the probability of child stunting by -0.5 controlling for other covariates. The paper recommends to the DRC's Ministry of public health to reinforce the parent's education, especially mothers of children, on the importance of infant and young child feeding practices for the nutrition of their children.
Keywords: 330; Feeding practices; Children's nutritional outcomes; Instrumental variable; Control functions approach; Democratic Republic of Congo